The Implementation of the Communicative Approach in Teaching English: A Qualitative Study at British English School Makassar - Syamsuddin, Syamsuddin; Ruing, Fentry Hernaningsi (Faculty of Education and Teacher Training of UIN Palopo, 2025)
This study investigates the implementation of the communicative approach in teaching English at British English School Makassar, Indonesia. Unlike most existing studies on Communicative Language Teaching (CLT) in Indonesia, which predominantly examine formal secondary or higher education settings, this study offers a context-specific analysis of CLT practices within a private language school. Employing a qualitative research design, the study involved three English teachers and thirty students selected through purposive sampling. This study concludes that the communicative approach is pedagogically effective in enhancing students’ speaking and listening skills through communicative classroom practices that promote active participation and authentic language use. Teachers and students generally perceived the approach positively, reporting increased confidence and willingness to use English, although student engagement varied according to prior learning experiences and linguistic readiness. Nevertheless, the implementation of the communicative approach was shaped by contextual constraints, including large class sizes, limited access to authentic instructional resources, learners’ previous exposure to teacher-centered instruction, differing proficiency levels, affective barriers, and time limitations. This study contributes novel empirical evidence to the CLT literature by illuminating how communicative principles are adapted, negotiated, and constrained within a private language school in Makassar as an underrepresented context in Indonesian EFL research.